Assessing Asia - Sub-Saharan Africa global value chain linkages - Heiwai Tang; Douglas Zhihua Zeng; Albert G. Zeufack (Kiel Institute for the World Economy (IfW), 2020)
This paper studies the relationship between Asia's economic engagements in Africa and individual African nations' participation in global value chains (GVC) over the past two decades. We find that while overall exports from Africa to Asia are still highly concentrated in resource-intensive sectors, a few African countries have exploited the emerging opportunities to diversify export portfolios through exporting to Asia. Each African nation has a distinct main trade partner in Asia, in contrast to the common view that China has become the dominant trade partner of most African nations. Using a panel data set for 46 African countries over 16 years from 2000 and 2015, we find that exports to Asia are positively correlated with exports to the rest of the world, suggesting that in contrast to trade diversion, trade with Asia complements exports to other countries. Asian economic engagement in the continent is associated with countries' exports 'moving up the value chain', as measured by the upstreamness index proposed by Antras et al. (2012). However, such process was accompanied by a reduction in the length of their production chains, implying that fewer stages and countries are now involved in the production of exported goods.
Keywords: F1; L6; O1; 330; Global Value Chains; Trade; Industrialization; Asia; Africa; Economic Development